PELUANG DAN TANTANGAN PENGGUNAAN ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN BIOKIMIA - Mahmudah, Rafiah (Hybrid: Jurnal Pendidikan dan Pembelajaran Sains, 2023)
Opportunities and Challenges of Using AI (Artificial Intelligence) in Biochemistry Learning aims to describe how artificial intelligence (AI) has been widely applied in education. Artificial intelligence in education (AIEd) opens up new opportunities, potentials and challenges in educational practice. In its short history, AIEd has undergone several paradigmatic shifts, which are characterized into three paradigms in this journal position: AI-directed, the learner as recipient, AI-supported, the learner as collaborator, and AI-empowered, the learner as leader. Within these three paradigms, AI techniques are used to address Biochemistry education and learning problems in various ways. AI is used to represent knowledge models and direct cognitive learning while learners are recipients of AI services in Paradigm One; AI is used to support Biochemistry learning while learners work as collaborators with AI in Paradigm Two; AI is used to empower learning while learners take the role to learn in Paradigm Three. Overall, the development trend of AIEd has evolved to empower learner education and personalization programs, enable learners to reflect on Biochemistry learning and inform AI systems to adapt, and lead to the iterative development of learner-centered, learner-driven Biochemistry learning.